"The Application of the Coaching Method in Islamic Religious Education Learning at South Mandioli State Junior High School, South Halmahera Regency" (Eurasian Journal of Learning and Academic Teaching, 2026)
This study aims to analyze the implementation of the coaching method in Islamic Religious Education learning at junior high schools in Mandioli Selatan District, South Halmahera Regency. The coaching method is a learning approach that emphasizes reflective questioning to help students develop understanding and explore their potential independently. This study employed a qualitative approach with a descriptive research design. The research was conducted at SMP Negeri 65, SMP Negeri 66, and SMP Negeri 72 South Mandioli. The research subjects consisted of Islamic Religious Education teachers and students. Data were collected through observation, interviews, and documentation. The data analysis used an interactive analysis model which includes data reduction, data display, and conclusion drawing. The results of the study indicate that the implementation of the coaching method in Islamic Religious Education learning is carried out through several stages, including determining learning goals, exploring students' initial understanding, providing reflective questions to encourage discussion and critical thinking, and conducting learning reflection at the end of the lesson. The implementation of the coaching method encourages students to be more actively involved in the learning process, increases their confidence in expressing opinions, and helps them understand the learning material more deeply. However, the implementation of the coaching method has not been fully consistent because in some learning situations teachers still use the lecture method to explain certain materials. Therefore, the coaching method has significant potential to improve the quality of Islamic Religious Education learning through active student participation in the learning process.